Measuring the Effectiveness of Civil Society: A Quantitative analysis of perceptions of stakeholders - HABIB, SHAHID (The journal of contemporary issues in business and government, 2020)
Civil society played significant role in strengthening democracy and good governance. The purpose of the current paper was to analyses the effectiveness of the civil society and examine the relationship between the dependent (civil society effectiveness) and independent variables (civic engagement, civic participation, civic association, and co-operation/ partnership). A survey questionnaire was distributed to all the seven categories of participants, and in response of 650 questionnaires 600 were received back. For empirical verification, in depth statistical tests were applied, including Standard Regression, Structural Equation Model (SEM), One Sample T-test, and correlation to test various assumptions of the study. Statistical analysis revealed that independent variables significantly contributed to the dependent variable. This study signifies the impact of independent variables (civic engagement, civic participation, civic association, and co-operation/ partnership) to achieve the effectiveness of civil society. Along with this, both (national and international) databases have been used for the qualitative analysis. Therefore, databases and survey results showed similar results. This research revealed that civil society does not hold good history in Pakistan. Both civilian and military dictators did not give free space to the civil society in the country. This showed that civil society organizations had a limited political space in the country. Therefore, CSOs have limited impact on policy making and implementation. We recommend that civil society should move beyond the awareness raising to mitigate the conditions conducive to spread of terrorism and extremism, which include marginalization, injustice, and violation of human rights, lack of rule of law, fragile democratic culture, and poor governance.